SIMULATION OF BASIC PHYSICS LEARNING MODEL THINK- PAIR-SHARE MODEL USING CROCODILE PHYSICS 605 BUDI DARMA UNIVERSITY - Melda Panjaitan (Sean Institute, 2023)
Think Pair Share learning is expected to help in the process of teaching basic physics at Budi Darma University, interactive simulation learning aims to support the independence of individual and group sharing for students in analysing the basic concepts of theory, calculations in the form of simulations and can be applied to everyday life. For this reason, it is necessary to use media, namely Crocodile physics 6.0.5 programming in simulating basic physics material. From this can be taken data analysis of the calculation of the extent to which the success of students can understand and accept the basic physics lecture material with the use of learning using existing simulation programming.